The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/2017ja023989
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional modeling of lightning‐induced electromagnetic pulses on Venus, Jupiter, and Saturn

Abstract: While lightning activity in Venus is still controversial, its existence in Jupiter and Saturn was first detected by the Voyager missions and later on confirmed by Cassini and New Horizons optical recordings in the case of Jupiter, and recently by Cassini on Saturn in 2009. Based on a recently developed 3‐D model, we investigate the influence of lightning‐emitted electromagnetic pulses on the upper atmosphere of Venus, Saturn, and Jupiter. We explore how different lightning properties such as total energy relea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…(2014) estimated that for Jupiter the peak photon density for elves would be at an altitude of 250–300 km, and Pérez‐Invernón et al. (2017) found that the width of elves in Jupiter's atmosphere could be between ∼400 km for horizontal discharge and ∼800 km for vertical discharge. For both sprites and elves, the characteristic decay times can vary from submillisecond to several milliseconds, depending on the parameters used in the model (Dubrovin et al., 2014; Luque et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…(2014) estimated that for Jupiter the peak photon density for elves would be at an altitude of 250–300 km, and Pérez‐Invernón et al. (2017) found that the width of elves in Jupiter's atmosphere could be between ∼400 km for horizontal discharge and ∼800 km for vertical discharge. For both sprites and elves, the characteristic decay times can vary from submillisecond to several milliseconds, depending on the parameters used in the model (Dubrovin et al., 2014; Luque et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Possible extrasolar lightning tracer are chemical species like HCN and C2H (Rimmer & Helling 2016;Hodosán et al 2016b;Ardaseva et al 2017), or spectral peculiarities like lightning modulated coherent cyclotron emission coming from electrons that are accelerated by the planet's magnetic field (Vorgul & Helling 2016;Helling & Vorgul 2017) similar to the lightning modulated cosmic ray air showers recently discovered on Earth (Schellart et al 2015;Trinh et al 2017). Moreover, strong large-scale magnetic fields like on Saturn (or Brown Dwarfs) enhance lightning-induced electric fields producing strong transient optical emission as demonstrated for Earth (Pérez-Invernón et al 2017). As lightning requires the presence of clouds, lightning indicators are formidable tool to prove the presence of clouds in exoplanet atmosphere as well as gaining insight into the atmospheric dynamics.…”
Section: Lightning On Exoplanet and The Extrasolar Global Electric Ci...mentioning
confidence: 96%
“…As in the model of halos, we can choose the characteristics of the lightning discharge that produces the elve. The details of this elve model can be found in Inan et al (), Taranenko et al (), Kuo et al (), Marshall et al (), Inan and Marshall (), Luque et al (), Marshall et al (), Pérez‐Invernón et al (), Liu et al (), and Pérez‐Invernón et al ().…”
Section: Electrodynamical Modelsmentioning
confidence: 99%